1995
DOI: 10.1126/science.7863326
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Specificity in the Recognition of MHC Class I by Natural Killer Cell Clones

Abstract: Recognition by natural killer (NK) cells of major histocompatibility complex (MHC) class I molecules on target cells inhibits NK-mediated lysis. Here, inhibition of NK clones by HLA-B*2705 molecules mutated at single amino acids in the peptide binding site varied among HLA-B*2705-specific NK clones. In addition, a subset of such NK clones was inhibited by only one of several self peptides loaded onto HLA-B*2705 molecules expressed in peptide transporter-deficient cells, showing that recognition was peptide-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
186
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 292 publications
(197 citation statements)
references
References 30 publications
10
186
1
Order By: Relevance
“…Peptide specificity in the recognition of MHC class I by NK cell clones has previously been reported for inhibitory KIR receptors. HLA-B*2705 interaction with KIR3DL1 shows some degree of peptide specificity, with residues at positions 7 and 8 identified as critical for the recognition [10,15]. Binding of soluble KIR2DL1 to HLA-Cw4 only occurred when the MHC class I molecule was loaded with peptides, and certain substitutions at position 7 and 8 abolished the interaction [11].…”
Section: Substitution At Position 8 Abolishes Kir3dl2 Interaction Witmentioning
confidence: 99%
“…Peptide specificity in the recognition of MHC class I by NK cell clones has previously been reported for inhibitory KIR receptors. HLA-B*2705 interaction with KIR3DL1 shows some degree of peptide specificity, with residues at positions 7 and 8 identified as critical for the recognition [10,15]. Binding of soluble KIR2DL1 to HLA-Cw4 only occurred when the MHC class I molecule was loaded with peptides, and certain substitutions at position 7 and 8 abolished the interaction [11].…”
Section: Substitution At Position 8 Abolishes Kir3dl2 Interaction Witmentioning
confidence: 99%
“…Binding of the KIR3DL1 receptor to the Bw4 family of MHC class 1 receptors has been shown to be dependent both on key residues of the a-1 helix around Ile80, and also on bound peptide [18]. Peruzzi et al studied NK recognition of B*2705-transfected RMAS cells loaded with peptide analogues of a (protective) self-peptide FRYNGLIHR, and showed that substitution of the P7I for A, D or R reduced protection from lysis [20].…”
Section: Kir3dl1 Sensitivity To the Ebv Peptide P8 Side Chainmentioning
confidence: 99%
“…Evidence indicates that KIR3DL1 binds the MHC a1 helix around residues 76-80, with specificity for all Bw4 alleles containing threonine at heavy-chain residue 80 [17]. In the case of HLA-B*2705 at least, KIR3DL1 also has specificity for bound peptide, showing greatest sensitivity for the residue at position 8 [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Viral peptides modulate recognition of HLA-B27 by NK receptors KIR3DL1 recognizes HLA-B*2705, interacting with residues around position 80, and with peptide residues 7 and 8 [24][25][26]. The crystal structure of this receptor is not known, but its interaction with B*2705 can be inferred from the structures of the KIR2DL2-HLA-Cw3 and KIR2DL1-HLA-Cw4 complexes [27,28].…”
Section: Hla-b27 Binding and Antigenic Features Of Immunodominant Virmentioning
confidence: 99%